The impact of surface chemistry on macrophage polarisation - Rostam, Hassan Muhammad (2017)
Background: Antigen presenting cells (APCs) such as macrophages play a crucial role in orchestrating immune responses against foreign materials. The activation status of macrophages can determine the outcome of an immune response following implantation of synthetic materials, towards either healing or inflammation. A large range of biomaterials are used in the fabrication of implantable devices and drug delivery systems. These materials will be in close contact with APCs and characteristics such as surface chemistry may have a critical role in polarising macrophages towards pro- or anti-inflammatory immune phenotype. Each phenotype can be characterised by their cytokine profile, transcription factors, surface markers or even morphology. Objectives: The overall objective of this study was identifying novel chemistries that are able to induce differentiation of human monocytes towards macrophages with distinct pro or anti-inflammatory phenotypes. To achieve this, a combination of different surface chemistries has been generated using oxygen plasma etching as well as acrylate and acrylamide polymer libraries. Methods: Fluorescent microscopy, real time-PCR, multiplex assay, ELISA, macrophage phagocytic activity were used for macrophage phenotype identification. Libraries of acrylates and acrylamide polymer microarrays (first generation microarray of 141 polymers and second generation of 442 polymers), and oxygen plasma etching of polystyrene used as two different techniques for making different surface chemistries. CellProfiller software was used for analysing images and was used for machine learning for phenotype identification. Results: polystyrene with highly hydrophobic surfaces are shown to suppress expression of M1-associated surface markers and cytokines while promoting M2-associated markers. However, highly hydrophilic surfaces seem to have the opposite effect as evidenced by promoting M1-associated marker expression and pro-inflammatory cytokine production while suppressing M2-associated marker expression and anti-inflammatory cytokine production. Also, the protein thickness was proportional with the hydrophilicity of the surface, which had impact on cell polarisation. Furthermore, co-polymers 157 from the second generation array was the most M2 biased polymer among the first and second generation of microarray polymers by induction of MR (M2 marker) cell expression, while co-polymers 217 and 123 from the second generation had impact to increase calprotectin (M1 marker). Also, cell adherence and morphology were affected by polymers surface chemistry. Conclusion: Surface chemistry without using polarising cytokine can polarise macrophage towards pro-inflammatory and anti-inflammatory phenotypes.